The role of dipotassium ethylenediaminetetraacetic acid and potassium oleate on chemical mechanical planarization relevant to heterogeneous materials of cobalt interconnects. (15th June 2023) - Zhang, Lifei; Wang, Tongqing; Wang, Shuhui; Lu, Xinchun
Abstract: Cobalt (Co) with its low resistivity, superior adhesion property, and void-free seamless fill ability, pledges to transform the landscape of integrated circuits in many areas, especially in interconnects and logic contacts. The present work describes the selection and optimization process of the complexing agent and inhibitor in chemical mechanical polishing barrier slurries relevant for heterogeneous materials of Co interconnects. An alkaline colloidal silica based slurry has been proposed, consisting of 0.5 wt% hydrogen peroxide, 5 mM dipotassium ethylenediaminetetraacetic acid (EDTA-2K), 13 mM potassium oleate (PO) and producing a Co removal rate of 45.6 Å/min, along with an appropriate removal rate selectivity between oxide dielectric, barrier layer and Co, which reaches above ∼ 2:1:1. Furthermore, synergetic effects of the oxidizer, complexing agent EDTA-2K and inhibitor PO on the Co CMP process have been investigated systematically by several analytical techniques, including electrochemical analysis, X-ray photoelectron spectroscopy survey, and adsorption isotherm characterization. The role of EDTA-2K affecting SERs and MRRs embodies in its strong complexing ability by dissociating to full deprotonated EDTA ion and then reacting with Co to produce very stable chelate Co(Ⅱ)EDTA. Moreover, the effect of inhibitor PO has a critical point. With the addition of PO at a low concentration, an effective passivation layer could be formed on Co surfaces spontaneously via chemisorption, protecting Co from severe pitting corrosion. While in case of PO at high concentration, Co(Ⅱ)PO ligand will be generated, reducing the stability of the original PO-Co passive layer and providing paths for complexing agent EDTA-2K to produce Co(Ⅱ)EDTA chelate.